INFLUENCE OF IRRIGATION SYSTEMS AND COVER CROP ON WATER PRODUCTIVITY, AND MAIZE GROWTH - AL-ARIDHEE, A. H. A.; N. T. MAHDI (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
A field experiment was carried out to assess the effect of different irrigation systems, which included surface drip irrigation, sub-surface drip irrigation, surface irrigation in basins and cover crop on water productivity, growth and yield of maize in a silty clay loam soil in the Nile sub-district of  Babil Governorate, in the fall season 2020. The experiment was designed using the split plot arrangement according to a complete randomized block design (RCBD) with three replications. The experiment treatments included two factors: cover crop (C) includes cover crop (C1) and without the cover crop (C0), and irrigation systems (I): includes surface drip irrigation (I1) subsurface drip irrigation (I2) and surface irrigation in basins (I3). Scheduling Irrigation was applied after 50% depletion of the plant available water. The water balance equation was used to determine the water consumption of maize. The results showed that C1I3 treatment was highest mean of plant height 235 cm, grain yield 11236 kg ha-1, leaf area 6076 cm2 plant-1, and leaf area index 4.05. Whereas, C0I1 was the lowest values for the previous traits, 183 cm, 5200 kg ha-1, 3997 cm2 plants-1, and 2.67 respectively. Treatment C1I2 was superior in the value of field water use efficiency and crop water use efficiency, which reached 3.49 kg m-3 and 3.05 kg m-3, respectively. Whereas, treatment C0I1 gave the lowest value for field and crop water use efficiency, which was 1.11 kg m-3 and 1.05 kg m-3, respectively. The highest water consumption of maize was 709 mm season-1 was for treatment C0I3, and the lowest water consumption was 362 mm season-1 for the treatment C1I2. It is clear that surface drip irrigation in the presence of cover crop contributed to saving irrigation water by reducing water consumption of maize.